ANALISIS KEMANDIRIAN BELAJAR SISWA MELALUI PEMBELAJARAN DARING PADA MATA PELAJARAN MATEMATIKA - Faisal Suleang; Nancy Katili; Siti Zakiyah (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2020)
This study aims to analyze the independent learning of students in mathematics through e-learning in class IX SMP Negeri 10 Gorontalo. This research is a descriptive research type, with a population of all class IX students of SMP Negeri 10 Gorontalo, totaling 101 students, consisting of 4 classes. The sample in the study was 20 people using a simple random sampling technique. The data obtained were obtained from student learning independence questionnaire sheets, as well as interviews with students related to students' learning independence in mathematics through e-learning. Based on the results of the research and discussion that the researcher has described in the previous chapter, that the learning independence of students in mathematics through e-learning is seen based on five indicators of learning independence divided into three categories namely high, medium and low categories. There are 4 high category students with an answer percentage of 20%. Second, there are 13 students belonging to the medium category with an answer percentage of 65%. Third, there are 3 students in the low category with an answer percentage of 15%. Of the three categories, in general, students only fulfill part of the indicators of learning independence measured in this study. So based on this, it can be concluded that the independent learning of students in mathematics through e-learning in class IX SMP Negeri 10 Gorontalo is still classified as moderate, so it needs to be improved.